OBLA is a better predictor of performance than Dmax in long and middle-distance well-trained runners - Santos-Concejero, J.; Granados, C.; Irazusta, J.; Bidaurrazaga-Letona, I.; Zabala-Lili, J.; Tam, N.; Gil, S. M. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The main purpose of this study was to investigate if the lactate threshold estimated by the maximal deviation method (LTDmax) and the onset of blood lactate accumulation speed (LTOBLA) are good correlates of middle- and long-distance running performance in well-trained endurance runners.